IMPLEMENTATION OF THE INDEX CARD MATCH STRATEGY IN IMPROVING LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION - Ikmah, Amit Dana; Neni, Titin Erviana Ayu; Novitasari, Dwiana; Azmi, M. Ulul; Islam, Muhammad Thoriqul (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
Teacher creativity in using learning strategies significantly influences student engagement and learning outcomes. This study examines the effectiveness of the Index Card Match strategy in improving learning outcomes in Islamic Religious Education at Sukorambi State Middle School. The problem identified was the dominance of lecture and discussion methods, which led to decreased student enthusiasm and achievement. The research aimed to explore how planning, implementing, and evaluating learning using the Index Card Match strategy could enhance student outcomes. Using a qualitative descriptive approach with purposive sampling, data were collected through observation, interviews, and documentation. Data analysis included data condensation, data presentation, and conclusion drawing, with validity ensured through source and technical triangulation. The findings revealed that learning planning involved syllabus preparation, detailed lesson plans, and the use of card-based learning media designed for active student participation. During implementation, the strategy was applied in core learning activities, promoting student engagement through interactive learning. Evaluation focused on assessing cognitive and affective aspects, ensuring a comprehensive understanding of the material. The study concludes that the Index Card Match strategy effectively enhances student engagement and learning outcomes in Islamic Religious Education, addressing the limitations of traditional methods. This strategy provides a more dynamic, student-centered learning experience, making it a valuable approach for educators. Kreativitas guru dalam menggunakan strategi pembelajaran memiliki pengaruh signifikan terhadap keterlibatan siswa dan hasil belajar. Penelitian ini mengkaji efektivitas strategi Index Card Match dalam meningkatkan hasil belajar Pendidikan Agama Islam di SMP Negeri Sukorambi. Masalah yang diidentifikasi adalah dominasi metode ceramah dan diskusi yang menyebabkan penurunan antusiasme dan pencapaian siswa. Penelitian ini bertujuan untuk mengeksplorasi bagaimana perencanaan, pelaksanaan, dan evaluasi pembelajaran menggunakan strategi Index Card Match dapat meningkatkan hasil belajar siswa. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik purposive sampling. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data meliputi kondensasi data, penyajian data, dan penarikan kesimpulan, dengan validitas data dijamin melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa perencanaan pembelajaran melibatkan penyusunan silabus, modul ajar, dan penggunaan media pembelajaran berbasis kartu yang dirancang untuk meningkatkan partisipasi aktif siswa. Pada tahap pelaksanaan, strategi diterapkan dalam kegiatan inti pembelajaran, yang mendorong keterlibatan siswa melalui pembelajaran interaktif. Evaluasi difokuskan pada penilaian aspek kognitif dan afektif untuk memastikan pemahaman materi secara komprehensif. Penelitian ini menyimpulkan bahwa strategi Index Card Match efektif dalam meningkatkan keterlibatan dan hasil belajar siswa pada Pendidikan Agama Islam, mengatasi keterbatasan metode tradisional. Strategi ini memberikan pengalaman belajar yang lebih dinamis dan berpusat pada siswa, sehingga menjadi pendekatan yang berharga bagi pendidik.